Influence of heliogeophysical disturbances on cardiac infarction, hypertensic crisis, psychological disturbance and behavioral disorders, bronchial asthma, cerebrovascular accident in Almaty - Nurgaliyeva, K. E.; Sadykova, A. M.; Akberdiyev, B.; Kisan, A.; Kosherbayeva, S. (International Journal of Mathematics and Physics, 2015)
In this work the dependence of frequency of cardiac infarction, hypertensic crisis, psychological disturbance and behavioral disorders, bronchial sthma, cerebrovascular accident in Almaty on solar and magnetic activity at the period 2009-2013 was investigated. During this period there were 694336 cases of calls for emergency help. In order to appreciate the level of solar and geomagnetic activity Wolf number and k-index was used. Data was nalysed by statistical method epochs superposition in order to find the correlations between geomagnetic activity and occurrence of listed above diseases. As the result it was established that in the day of magnetic storm and two days after number of patients directed to hospital with psychological disturbance and behavioral disorders increases. Number of patients directed to hospital with cardiac infarction increases the day before and remains some days after. Number of patients directed to hospital with hypertensic crisis increases in the day of magnetic storm. Number of patients directed to hospital with cerebrovascular accident increases a day after magnetic storm. What concerns of bronchial asthma the dependence is not so clear.